2015
DOI: 10.1002/jcp.25282
|View full text |Cite
|
Sign up to set email alerts
|

E11/Podoplanin Protein Stabilization Through Inhibition of the Proteasome Promotes Osteocyte Differentiation in Murine in Vitro Models

Abstract: The transmembrane glycoprotein E11 is considered critical in early osteoblast–osteocyte transitions (osteocytogenesis), however its function and regulatory mechanisms are still unknown. Using the late osteoblast MLO‐A5 cell line we reveal increased E11 protein/mRNA expression (P < 0.001) concomitant with extensive osteocyte dendrite formation and matrix mineralization (P < 0.001). Transfection with E11 significantly increased mRNA levels (P < 0.001), but immunoblotting failed to detect any correlative increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 62 publications
4
26
0
Order By: Relevance
“…Conversely, the ectopic overexpression of Pdpn in keratinocytes induces plasma membrane extensions (Scholl, Gamallo, Vilaro, & Quintanilla, ), and in endothelial cells, the reorganization of the actin cytoskeleton and the formation of long tube like structures (Schacht et al, ). Similarly, we have previously shown that stabilization of Pdpn protein, through inhibition of endogenous proteasome activity, promotes dendrite formation through the RhoA/ROCK/ERM pathway (Staines, Prideaux, et al, ). RhoA is a small GTPase and a master regulator of various cellular processes such as cytokinetics, cytoskeletal regulation, and cell migration (Takai, Sasaki, & Matozaki, ).…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Conversely, the ectopic overexpression of Pdpn in keratinocytes induces plasma membrane extensions (Scholl, Gamallo, Vilaro, & Quintanilla, ), and in endothelial cells, the reorganization of the actin cytoskeleton and the formation of long tube like structures (Schacht et al, ). Similarly, we have previously shown that stabilization of Pdpn protein, through inhibition of endogenous proteasome activity, promotes dendrite formation through the RhoA/ROCK/ERM pathway (Staines, Prideaux, et al, ). RhoA is a small GTPase and a master regulator of various cellular processes such as cytokinetics, cytoskeletal regulation, and cell migration (Takai, Sasaki, & Matozaki, ).…”
Section: Discussionmentioning
confidence: 63%
“…We, and others, have previously shown that Pdpn promotes osteocytogenesis and dendrite formation in vitro (Staines, Prideaux, et al, ; Zhang et al, ). Our studies, described herein, have for the first time successfully generated a bone‐specific conditional Pdpn hypomorphic mouse and we have confirmed a role for Pdpn in the attainment of fully elongated osteocyte dendrites.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…We, and others, have previously highlighted the requirement for the transmembrane glycoprotein E11/podoplanin (Pdpn) to make the cytoskeletal network modifications that are critical for the formation of dendrites during osteocytogenesis. This role is consistent with its expression by early embedding osteocytes, thus identifying Pdpn as a factor which likely contributes to the vital, early stages of osteocyte differentiation [11]. Furthermore, Pdpn expression in osteocytes is increased in response to mechanical strain in vivo [12] and the formation of dendritic processes is promoted by both Pdpn overexpression and through its stabilisation by proteasome inhibitors [11,13].…”
Section: Introductionmentioning
confidence: 72%
“…Differentiation of cultured mouse calvarial osteoblasts and pre-osteoblastoid cell MLO-A5 into osteocytes in calcification medium containing βglycerophosphate and ascorbic acid, and biomaterial-induced calcification are simultaneously accompanied by an increase in podoplanin (24)(25)(26)(27). Also, in the mature osteoblast MLO-A5 cell line, an increase in podoplanin coincides with dendrite formation, calcification, and RhoA activation (28).…”
Section: Introductionmentioning
confidence: 95%